Analysis of the Satisfaction Level of Gojek (GoFood) Application Users in Rawalumbu, Bekasi City Using the PIECES Framework During Pandemic Period - Septina, Patricia Lorraine; Sihotang, Jay Idoan (8ISC Proceedings: Technology, 2022)
The problems studied arise from users regarding the facilities used and obtained from the Gojek application. Many aspects are taken into consideration by consumers in choosing and deciding which application to use. An important aspect that is considered by consumers is satisfaction with service quality in meeting consumer needs and desires, which are still uncertain. The data collection technique used by the researcher is a questionnaire. The population in this study are users of the Gojek application in Rawalumbu, Bekasi City, with a sample of 100 respondents using the Lemeshow formula. The PIECES Framework method provides tangible results on the effectiveness of the Gojek (GoFood) application system by analyzing the Performance, Information, Economics, Control & Security, Efficiency, and Service variables. Calculation of the results of the questionnaire using a Likert Scale to measure the respondent’s perception or opinion of a condition is then made in the form of a percentage using the Customer Satisfaction Index. The percentage of satisfaction level for each variable, namely, the Performance variable gets an index value of 86.40%, the Information variable gets an index value of 85.80%, Economics gets an index value of 84.60%, the Control and Security variable gets an index value of 83.00%, the variable Efficiency gets an index value of 88.40%, and Service gets an index value of 86.40%. So the results of this study are the total average level of satisfaction from all domains, namely getting an index value of 85.76% (Very Satisfied). Keywords : Gojek Application, Gofood, PIECES Framework, Customer Satisfaction Index